SOSIALISASI PENTINGNYA KESADARAN HUKUM TERHADAP PINJAMAN ONLINE - YAYAN ROSANTO,,; TEGAR HARBRIYANA PUTRA, (KRIDA CENDEKIA, 2022)
The dynamics of globalization and transformation of the technology information which grow rapidly among the society has changed the social and economic order. The technologycal sophistication eases people to accessthe information they need, one of them is by using Information Technology-Based Lending and Loan Services or known as Online Loans. Online Loan is money lending online facilities by financial service providers. The online provider is known as fintech, online loans whose funds can be immediately disbured without colleteral is an alternative solution for people who need cash without applying in person. The approach method used in this paper is empirical normative based on (“POJK NO. 77/PJOK.01/2016”). Besides as a temporary solution, online loan has impacts and risks unrecognized by the society. The purpose of this socialization intends to build legal awareness regrading the impavts and risks the arise from online loan, especially for member Karang Taruna Janglot, Songbledeg, Paranggupito, Wonogiri. Thus, this activity contributes to give insight for society, especially for Karang Taruna youth to respond wisely in utilizing both legal and illegal online load applications.